2020
DOI: 10.1108/ijmpb-04-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of research and industry views on project managers’ competencies

Abstract: Purpose The success of projects clearly relies on project management personnel and particularly on project managers. Their performance and capacities are based on the achieved competencies. The purpose of this paper is to address possible discrepancies between the views arising from the research results and standards of practice related to project managers’ competencies. Design/methodology/approach For reaching the aim of the study, a comprehensive literature review, covering previous studies and related sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 60 publications
2
34
0
3
Order By: Relevance
“…The general competency standards are broadly adopted based on performance instead of knowledge (Crawford, 2005; Hanna et al, 2016; Moradi et al, 2020a). The standards are; the International Project Management Association’s (IPMA) standards, the Project Manager Competency Development (PMCD) Framework by Project Management Institute (PMI) based on PMBOK Guide (Project Management Institute, 2008), and National Competency Standards for Project Management by the Australian Institute of Project Management (AIPM).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The general competency standards are broadly adopted based on performance instead of knowledge (Crawford, 2005; Hanna et al, 2016; Moradi et al, 2020a). The standards are; the International Project Management Association’s (IPMA) standards, the Project Manager Competency Development (PMCD) Framework by Project Management Institute (PMI) based on PMBOK Guide (Project Management Institute, 2008), and National Competency Standards for Project Management by the Australian Institute of Project Management (AIPM).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The general competency standards are broadly adopted based on performance instead of knowledge (Crawford, 2005;Hanna et al, 2016;Moradi et al, 2020a (Project Management Institute, 2017). These competency standards have been broadly used to evaluate a project manager's role with the assumptions that: (i) managerial practices are universal and context-independent, and (ii) project manager's performance can be led by certified PMs based on Competency Standards (Chen et al, 2008;Crawford, 2005;Hanna et al, 2016).…”
Section: Project Manager Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, although the notion of project managers' behavioral competencies has gained growing interest in recent years, we find that there is a dearth of quantitative analysis in this domain. Specifically, prior research has examined behavioral competencies in different ways: Dogbegah et al (2011) and Othman and Jaafar (2013) conducted a comprehensive literature review to understand the most influential competencies for project success; Ara ujo and Drebes (2015) and Sang et al (2018) performed in-depth interviews with professional project managers to detect which competencies are the most important; Chipulu et al (2013) and Vale et al (2018) used a coding method and extracted the core competencies from job advertisements; and Moradi et al (2019) performed a comparison of research and industry views on project managers' competencies. However, studies adopting a quantitative approach that measures the influence of behavioral competencies on project success are rare.…”
Section: Ijmpb 151 192mentioning
confidence: 99%
“…The more recent studies conducted between 2015 and 2019 suggest that the focus on investigating and identifying project managers' competencies in construction projects has been continued [13,18,[51][52][53][54][55][56][57]. A recent study [20] concerning project managers' competencies has also shown that construction projects have been considerably focused on by the research community among the other specific project types for addressing project managers' competencies. Reviewing relevant studies resulted in a synthesis of 184 competencies of project managers for construction projects.…”
Section: Project Managers' Competencies In the View Of Research Commumentioning
confidence: 99%